Genome-Wide Analysis of Glycine soja Response Regulator GsRR Genes Under Alkali and Salt Stresses - Chen, Chao; Liu, Ailin; Ren, Hao; Yu, Yang; Duanmu, Huizi; Duan, Xiangbo; Sun, Xiaoli; Liu, Beidong; Zhu, Yanming (Frontiers in Plant Science, 2018)
Soil salt-alkalization is a dramatic challenging factor for plant growth. Wild soybean (Glycine soja) exhibits a favorable trait of superior tolerance to salt-alkali stress, and recent discoveries show that response regulator family genes are involved in diverse abiotic stresses. Genomic and transcriptomic analyses of all response regulator genes in wild soybean will provide insight into their function in plant stress response. In this study, we identified and characterized a total of 56 Glycine soja response regulator (GsRR) genes. Phylogenetic analysis suggested that GsRR genes could be classified into five subclasses (A1, A2, B1, B2 and C). We further investigated the chromosome locations, gene duplications and conserved domains of the GsRRs. Furthermore, the clustering analysis of GsRR transcript profiles revealed five different expression patterns under alkali stress. The A1 and A2 subclasses display significantly higher transcriptional levels than the B subclass. In addition, quantitative real-time PCR results verified that the GsRR genes were also significantly influenced by salt stress. Notably, GsRR2a in the A1 subclass showed opposite expression patterns under salt stress comparing with alkali stress. Moreover, overexpression of GsRR2a in Arabidopsis significantly improved the tolerance to alkali stress, but not salt stress. These results suggest the important roles of GsRR genes in response to salt and alkaline stresses, and also provide valuable clues for further functional characterization of GsRR family genes.